Grasping the semantic of actions: a combined behavioral and MEG study - Visani, Elisa; Garofalo, Gioacchino; Rossi Sebastiano, Davide; Duran, Dunja; Craighero, Laila; Riggio, Lucia; Buccino, Giovanni (Frontiers in Human Neuroscience, 2022)
There is experimental evidence that the brain systems involved in action execution also play a role in action observation and understanding. Recently, it has been suggested that the sensorimotor system is also involved in language processing. Supporting results are slower response times and weaker motor-related MEG Beta band power suppression in semantic decision tasks on single action verbs labels, when the stimulus and the motor response involve the same effector. Attenuated power suppression indicates decreased cortical excitability and consequent decreased readiness to act. The embodied approach forwards that the simultaneous involvement of the sensorimotor system in the processing of the linguistic content and in the planning of the response determines this language-motor interference effect. Here, in a combined behavioral and MEG study we investigated to what extent the processing of actions visually presented (i.e., pictures of actions) and verbally described (i.e., verbs in written words) share common neural mechanisms. The findings demonstrated that, whether an action is experienced visually or verbally, the processing of it engages the sensorimotor system in a comparable way. These results provide further support to the embodied view of semantic processing, suggesting that this process is independent from the modality of presentation of the stimulus, including language.